2001
DOI: 10.1677/jme.0.0260107
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization of the gene coding for human pre-B-cell colony enhancing factor and expression in human fetal membranes

Abstract: Pre-B-cell colony enhancing factor (PBEF) was first isolated from an activated peripheral blood lymphocyte cDNA library and was found to be involved in the maturation of B-cell precursors. It was subsequently identified as one of the genes upregulated by distending the human fetal membranes in vitro. Here we report on the genomic organization of this gene, which is composed of 11 exons and 10 introns, spanning 34·7 kb of genomic DNA. Neither the gene nor the protein has any homology with other cytokines in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
3
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(247 citation statements)
references
References 29 publications
6
231
3
7
Order By: Relevance
“…Chronic inflammation in the prostate gland, which produces reactive oxygen species, is an important etiological factor for prostate carcinogenesis (Nelson et al, 2003;De Marzo et al, 2007). Intriguingly, NAMPT is an inflammation-response gene, and its expression increases in multiple inflammatory tissues (Ognjanovic et al, 2001;Ye et al, 2005;Busso et al, 2008). That NAMPT expression is elevated early in prostate neoplasia suggests NAMPT may have a role in the etiology of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation in the prostate gland, which produces reactive oxygen species, is an important etiological factor for prostate carcinogenesis (Nelson et al, 2003;De Marzo et al, 2007). Intriguingly, NAMPT is an inflammation-response gene, and its expression increases in multiple inflammatory tissues (Ognjanovic et al, 2001;Ye et al, 2005;Busso et al, 2008). That NAMPT expression is elevated early in prostate neoplasia suggests NAMPT may have a role in the etiology of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elevated maternal visfatin concentrations in GDM at 2nd trimester may reflect an impairment of visfatin function in target tissues, dysregulation of biosynthesis, or a response to hyperglycemia [52]. On the other hand, TNF-a is known to enhance visfatin expression in human placental cells [53]. Thus, the placenta could be a source of increased visfatin in GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The biological relevance of overexpression of PBEF in CRC is unclear given the reported normal function of PBEF is in the maturation of B cell precursors. 20 More recent studies have shown the upregulation of PBEF in infected fetal membranes 22,23 and specific localization to normal fetal cells and also to invading neutrophils. 23 The PBEF gene contains multiple promotor sites responsive to different transcription inducing agents 23 that may account for differential expression of the protein in different tissues and also possibly differences in function.…”
Section: Use Of Peptide Specific Phage Antibodies As Probes For the Pmentioning
confidence: 99%